2020
DOI: 10.3390/toxins12090536
|View full text |Cite
|
Sign up to set email alerts
|

Immune Suppression Induced by Gallibacterium anatis GtxA During Interaction with Chicken Macrophage-Like HD11 Cells

Abstract: The RTX toxin GtxA expressed by Gallibacterium anatis biovar haemolytica has been proposed a major virulence factor during disease manifestations in the natural host, the chicken. To better understand the role of GtxA in the pathogenesis of G. anatis, we compared the GtxA expressing wildtype strain with its isogenic ∆gtxA mutant that was unable to express GtxA during exposure to chicken macrophage-like HD11 cells. From adhesion and invasion assays, we showed that GtxA appears to promote adhesion and invasion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Studies have shown that the Gtx A protein has a significant inhibitory effect on lymphocyte growth. It is also considered an important pathogenic factor, affecting cell permeability and the expression of inflammatory factors, causing cell damage and apoptosis and significantly mediating the pathogenesis of salpingitis in poultry [ 29 , 30 , 31 ]. These results are comparable to data previously presented by other authors [ 30 ], which also relate to the presence of another virulence gene often used to identify G. anatis infections in chickens and turkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the Gtx A protein has a significant inhibitory effect on lymphocyte growth. It is also considered an important pathogenic factor, affecting cell permeability and the expression of inflammatory factors, causing cell damage and apoptosis and significantly mediating the pathogenesis of salpingitis in poultry [ 29 , 30 , 31 ]. These results are comparable to data previously presented by other authors [ 30 ], which also relate to the presence of another virulence gene often used to identify G. anatis infections in chickens and turkeys.…”
Section: Discussionmentioning
confidence: 99%
“…The toxin is a specific virulence factor of G. anatis . Its presence gives G. anatis a means of adhering to cells and changes cell permeability and expression of inflammatory factors, resulting in cell damage and apoptosis ( 20 , 30 , 36 ). Kristensen et al ( 20 ) in their research concluded that Gtx A may represent a new form of RTX-like toxin with immune evasion function.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al ( 2020 ) implied that GtxA plays a crucial function in an acute cytokine-mediated Th2-like response versus G. anatis infection in the ovarian tissue, helping in the pathogenesis of G. anatis infections in laying hens. Additionally, Tang and Bojesen ( 2020 ) attempted to explain the immunosuppressive effect of G. anatis GtxA during the interaction with chicken macrophage-like HD11 cells by encouraging cell adhesion and invasion, reducing the host inflammatory response based on an initial over-expression of interleukin (IL)-10 and a corresponding low-level expression of tumor necrotizing factor (TNF)-α, and concluded that GtxA induces cell death (apoptosis) without revealing clear causes. Fimbriae.…”
Section: Virulence Factorsmentioning
confidence: 99%